Comparative study of Chitrikadi Vati and Medhya Vati on psychotic factor in Agni Dusti w.s.r. to Grahani Dosha - Mathur, Julee; Gupta, Piyush (International Research Journal of Ayurveda & Yoga, 2019)
ancient science Ayueveda has a apporh to the health is psychosomatic in nature. The primary principle of Ayurveda is dosha which is also divided in two parts that is sharirika dosh and manshika dosha. These both type of dosha are equally effects each other that’s manas bhavas are depend on sharirika bhavas and vice versa. Same as the causative factor of a disease may effects sharirika dosha , mansika dosha or both. In present study we are trying to stabilized relation between manas bhava and agni dusti W.S.R. to grahani dosha. So the present study Comparative study of chitrikadi vati and medhya vati on psychotic factor in agni dusti w.s.r. to Grahani dosha, has 3 groups. Group A contains Chitrikadi vati 2 tab. BD, Group B contains Medhya vati 2 tab. BD and Group C contains both Chitrikadi vati 2 tab. BD and Medhya vati 2 tab. BD. The data collection, analysis and conclusion drawn from it is elaborated in this article.